Association of macro-and micro-nutrients dietary intakes with rs2241883 genetic variants of FABP 1 gene in MASHAD study population. (October 2021) - Valizadeh, Mohsen; Aghasizadeh, Maliheh; Saberi-Karimian, Maryam; Safari, Mina; Rohban, Mohadese; Bana, Hamideh Safarian; Zare-Feyzabadi, Reza; Tavakkol Afshari, Haleh Sadat; Moradi, Ali; Ahangari, Najmeh; Hashemi, Mohammad; Nematy, Mohsen; et al.
Summary: Introduction: There is a relationship between macro-nutrient-intakes and the genes implicated in lipid metabolism. In this study, we assessed the association between macro-and micro-nutrients dietary intakes with rs2241883 genetic variants of the FABP1 gene. Methods: For this cross-sectional study 2737 subjects (including 2203 subjects with dyslipidemia and 534 healthy volunteers) were enrolled as part of the Mashhad Stroke and Heart Atherosclerotic Disorder (MASHAD) study cohort. Dyslipidemia was defined based on the National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III). A NanoDrop®-1000 instrument was used to do the quantitation of DNA. The rs2241883 polymorphisms were genotyped using double ARMs PCR reactions. Genotyping reagents were obtained from Applied Biosystems. Dietary intake was evaluated using a food frequency questionnaire (FFQ) and validated by 2 consecutive 24-h food recalls. Results: The results showed no significant association between subjects with and without dyslipidemia (P > 0.05), except for the zinc to copper ratio, the value for which was higher in the subjects with dyslipidemia (4.78 (1.62)) when compared to subjects without dyslipidemia (4.68 (1.82)) (p = 0.05). Using different genetic models we found that zinc and copper were significantly different in the additive (p = 0.01) and dominant (p = 0.01) genetic models. Although, this association was no longer significant after adjusting for confounding factors. Conclusions: There were no associations between macro-and micro-nutrient dietary intakes with rs2241883 genetic variants after adjusting for confounding factors in the MASHAD study population.